Expanding the scope of the anion templated synthesis of interlocked structures. - Spence, G; Beer, P (2013)
Nature achieves impressively strong and selective complexation of small molecule anions through the elaborate binding sites of sophisticated proteins. Inspired by these examples, we have developed an anion templation strategy for the synthesis of mechanically interlocked host structures for anion recognition applications. Upon removal of the discrete anionic templating species, such host systems possess unique, three-dimensional, geometrically restrained cavities containing convergent hydrogen bond donor atoms. Such structures exhibit high affinity binding selectivity toward complementary anions. This Account describes recent advances in this anion templation meth odology, demonstrating the versatility and scope of this approach, and progressing to more diverse architectures. Specifically, we have prepared an expansive range of interlocked hosts with enhanced anion recognition properties, such as the ability to operate effectively in competitive aqueous media. We have produced these structures through the utilization of a new anion templated amide condensation synthetic method and through the incorporation of a range of different anion binding motifs, such as groups capable of effective solution-phase halogen bonding interactions. Importantly, direct comparisons between halogen bonding and hydrogen bonding systems reveal impressively magnified anion recognition properties for halogen bonding interlocked host systems. We have also employed the anion templation strategy successfully to construct selective electrochemical and luminescent anion sensors, as well as architectures of increasing complexity, such as a triply interlocked capsule and a handcuff catenane. The synthesis of these latter examples presents greater challenges; however, such molecules offer additional applications in higher order recognition and sensing and in switchable molecular devices. Having established anion templation as a viable synthetic route to interlocked architectures, we have used this strategy to fabricate a multitude of innovative structures. The key principles of this approach are the ability of anionic species to template the association of carefully designed components, and of the resulting molecular framework with its interlocked host cavity to display impressive anion recognition selectivity. Mechanically interlocked structures have numerous potential applications in nanotechnology. Therefore, the continuing development of effective synthetic methods, especially those which yield functional systems, is of great interest in the broad interdisciplinary field of supramolecular chemistry.